2021
DOI: 10.3389/fdgth.2021.659940
|View full text |Cite
|
Sign up to set email alerts
|

Home Monitoring System for Comprehensive Geriatric Assessment in Patient's Dwelling: System Design and UX Evaluation

Abstract: Population aging threatens the sustainability of welfare systems since it is not accompanied by an extended healthy and independent period in the last years of life. The Comprehensive Geriatric Assessment (CGA) has been shown to be efficient in maintaining the healthy period at the end of the life. Frailty monitoring is typically carried out for an average period of 6 months in clinical settings, while more regular monitoring could prevent the transition to disability. We present the design process of a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The recommendation to favor video tutorials over written instructions matches our own experience in performing usability tests on eHealth apps for geriatric patients, wherein we observed users tiring easily from lengthy textual instructions [ 84 , 85 ]. Although the study by Ahmad [ 86 ] focused on younger tech-proficient adults (aged >50 years), it showed the user preference for video tutorials.…”
Section: Discussionmentioning
confidence: 77%
“…The recommendation to favor video tutorials over written instructions matches our own experience in performing usability tests on eHealth apps for geriatric patients, wherein we observed users tiring easily from lengthy textual instructions [ 84 , 85 ]. Although the study by Ahmad [ 86 ] focused on younger tech-proficient adults (aged >50 years), it showed the user preference for video tutorials.…”
Section: Discussionmentioning
confidence: 77%
“…15,16 mHealth interventions also produced some evidence of behavior change and improvements in clinical outcomes. 17 In our study, 43.3% of health care workers used mHealth applications for general practice at least once per week. for many important tasks, such as information and time management, health record maintenance and access, communications and consulting, reference and information gathering, patient management and monitoring, clinical decision-making, and medical education and training that can be used for general practice.…”
Section: Discussionmentioning
confidence: 69%
“…15 , 16 mHealth interventions also produced some evidence of behavior change and improvements in clinical outcomes. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows how the interaction system evolved during the process. An in-depth description of this iterative process and the resulting interaction system can be found in [51]. This interaction system was iteratively designed under a user-centered approach.…”
mentioning
confidence: 99%
“…Figure 4 shows how the interaction system evolved during the process. An in-depth description of this iterative process and the resulting interaction system can be found in [51]. Figure 5 shows the workflow that needs to be followed to interact with any of the components of the monitoring kit.…”
mentioning
confidence: 99%